Analisis Kesulitan Belajar Matematika Operasi Penjumlahan Dan Pengurangan Bilangan Cacah Pada Peserta Didik Kelas II B SD Inpres Ende 7 Kecamatan Ende Timur Kabupaten Ende - Jou Aman Johra (Ekspektasi: Jurnal Pendidikan Ekonomi, 2019)
This study aims to find out the difficulties and analyze errors in working on the addition and subtraction numbers of operation problems in class II B SD Inpres Ende 7 students. Data collection uses test techniques, analyzed by examining the work of students and analysis techniques percentage level of difficulty learners. Then grouped into the criteria of difficulty level of students who are modified from the criteria of understanding. The results of the research show the completion of the addition and subtraction calculation of counts that are not in accordance with mathematical propositions. There is a miscalculation because it does not include a save number obtained from the results of calculations, irregularities in working on short-sum addition problems, reduction calculation errors because it does not borrow numbers for small amounts before subtracting large numbers, and assume that the borrowed numbers remain as they were. Accumulation of learning difficulties in addition and subtraction numbers experienced by 17 participants in three categories (moderate to very high) of 3.74% and 2.23%. It was concluded that the difficulties (mistakes) made by students were a basic mistake of addition and random errors due to lack of mastery of the concepts of addition and subtraction, saving and borrowing techniques, and misconceptions in solving problems.